ANALISIS KEPRIBADIAN DAN MOTIVASI DALAM MENINGKATKAN MINAT BERWIRAUSAHA MAHASISWA POLITEKNIK LP3I JAKARTA KAMPUS CIKARANG - Niantoro Sutrisno; Saun Supriaman; Hadi Purnama (JURNAL LENTERA BISNIS, 2019)
In LP3I Jakarta – Campus Cikarang, most of students were not interested to the entrepreneurship. Thus, further research is needed to elaborate the personality and motivation which are having impact to the entrepreunership. The method of this research uses quantitative descriptive research. The population by taking from Regular Students of LP3I Jakarta – Cikarang Campus. Random sampling approach to determine sample, in this case, 73 students as a sample. Data collects through questionnaires for multiple regression analysis. The results of this study show that there is positive and significant influence of personality to the interest in entrepreneurship as indicated by the correlation coefficient (R) partially equal to 0.692 (strong). Motivation has positive and significant influence to the interesting in entrepreneurship as indicated by the correlation coefficient (R) partially equal to 0.639 (strong). Meanwhile, The simultaneously influence of personality and motivation to the interesting in entrepreneurship has positive and significant influence indicated by the correlation coefficient R = 0.754 or R² = (0.754) ² = 57% while the remaining 43% influenced by other variables was not examined.Keywords: Personality, Motivation, Interest, Entrepreneurship